Transition metal activation and functionalization of carbon-hydrogen bonds - Jones, W.D. (Rochester Univ., NY (United States), 1992)
We are investigating the fundamental thermodynamic and kinetic factors that influence carbon-hydrogen bond activation at homogeneous transition metal centers and the conversion of hydrocarbons into functionalized products of potential use to the chemical industry. Advances have been made in both understanding the interactions of hydrocarbons with metals and in the functionalization of hydrocarbons. We have found that RhCl(PRsub 3){sub 2}(CNR) complexes can catalyze the insertion of isonitriles into the C-H bonds or arenes upon photolysis. The mechanism of these reactions was found to proceed by way of initial phosphine dissociation, followed by C-H activation and isonitrile insertion. We have also examined reactions of a series of arenes with (Csub 5Mesub 5)Rh(PMesub 3)PhH and begun to map out the kinetic and thermodynamic preferences for arene coordination. The effects of resonance, specifically the differences in the Hueckel energies of the bound vs free ligand, are now believed to fully control the C-H activation/{eta}{sup 2}-coordination equilibria. We have begun to examine the reactions of rhodium isonitrile pyrazolylborates for alkane and arene C-H bond activation. A new, labile, carbodiimide precursor has been developed for these studies. We have completed studies of the reactions of (Csub 5Mesub 5)Rh(PMesub 3)Hsub 2 with Dsub 2 and PMesub 3 that indicate that both {eta}{sup 5} {yields} {eta}{sup 3} ring slippage and metal to ring hydride migration occur more facilely than thermal reductive elimination of Hsub 2. We have examined the reactions of heterocycles with (Csub 5Mesub 5)Rh(PMesub 3)PhH and found that pyrrole and furan undergo C-H or N-H activation. Thiophene, however, undergoes C-S bond oxidative addition, and the mechanism of activation has been shown to proceed through sulfur coordination prior to C-S insertion.